Vernacular Art seen in Taut’s Bamboo Weaving - Maejima, Yoshie (Journal of the Asia Ethno-Forms Association, 2022)
The purpose of this research is to explore the idea of Mr. Taut by focusing on the “Taut’s Bamboo weaving” craft created in Takasaki City when Mr. Bruno Taut came to Japan in the early Showa period. Taut's philosophy is clarified by understanding it from the remaining “Taut’s Bamboo weaving” crafts, designs, surveys with related parties, etc. Firstly, clarify the situation in Takasaki city when Mr. Taut was invited. Then, follow thecontents such as Takasaki's craft movement and “Taut’s Bamboo weaving”, innovation of “Taut’s Bamboo weaving”, the regional craft movement aiming for Takasaki's Bauhaus, the relationship between the climate of Japan and “Taut’s Bamboo weaving”, etc. in the other of scooping. The subject of this research is to clarify the deepening of the philosophy through “Taut’s Bamboo weaving” by understanding the Taut's admire for Asia as well as Japanese culture after he came to Japan. At last, we would like to thank the Gunma Prefectural Museum of History, Mr. Tatsuaki Tanaka, other researchers of Taut for their cooperation in this research.